Sickle cell disease and social determinants of health: A scoping review. Issue 2 (10th December 2022) - Khan, Hamda; Krull, Mathew; Hankins, Jane S.; Wang, Winfred C.; Porter, Jerlym S.
Abstract: Social determinants of health (SDoH) may impact outcomes in sickle cell disease (SCD). We conducted a comprehensive literature review of five electronic databases to elucidate the relationship between SDoH and SCD, and identify gaps in the literature. Our search yielded 59 articles, which we organized into five SDoH areas: Neighborhood and Built Environment, Health and Healthcare, Social and Community Context, Education, and Economic Stability. We found that social determinants, such as access to healthcare, were inconsistently evaluated. Improved recognition and understanding of SDoH should enhance the development of programs that directly address its detrimental effects on patients with SCD.